Individual and Technology Factors in Knowledge Sharing Model to Support Learning Performance and Learning Collaboration - AHMAD ALARABIAT, DEEMAH ABDEL KAREEM (2018)
Higher Education Institutions (HEIs) are knowledge intensive environments where students play an important role in leveraging knowledge resources. Recently, HEIs make significant investments in information and communication technology to establish effective Knowledge Sharing (KS) practices and to support KS among students. Simultaneously, current studies show that Mobile Learning (M-learning) and cloud computing (e.g., Software as a Service - ‘SaaS’) are important technologies that affect students learning, experience and performance.